2014
DOI: 10.1093/cid/ciu357
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Personal Contact With HIV Patients Improves Retention in Primary Care: A Randomized Trial in 6 US HIV Clinics

Abstract: CDCHRSA9272007.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
114
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 132 publications
(116 citation statements)
references
References 35 publications
2
114
0
Order By: Relevance
“…27,28,33 To our knowledge, interventions to improve trust in physicians have not been developed or tested. An alternative strategy to intervening to improve trust is to identify persons with low trust and then delivering retention interventions, such as enhanced personal contact, 34 to these patients. While it includes physicians, the healthcare system is broader and includes hospitals, clinics, insurers, and other entities.…”
Section: Discussionmentioning
confidence: 99%
“…27,28,33 To our knowledge, interventions to improve trust in physicians have not been developed or tested. An alternative strategy to intervening to improve trust is to identify persons with low trust and then delivering retention interventions, such as enhanced personal contact, 34 to these patients. While it includes physicians, the healthcare system is broader and includes hospitals, clinics, insurers, and other entities.…”
Section: Discussionmentioning
confidence: 99%
“…[28][29][30][31][32] Given the increasing pressure to manage large panels of complex patients in a manner that produces optimal outcomes with minimal use of resources, identifying ways to conduct population-level triage remains critical. In addition to predicting the magnitude of risk for missing the next appointment, this tool stratified a large cohort of over 500 patients with unsuppressed viremia based on severity of risk.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this study sought to determine whether a tool previously operationalized to stratify patients according to virologic failure risk at 1 year 27 could also stratify patients based on the risk of a related and potentially more immediate event: missing their next HIV primary care visit. Systematic risk assessment could support targeting of limited resources and interventions shown to improve engagement in care, such as enhanced case management, [28][29][30] to those at highest risk.…”
Section: Aids Patient Care and Stdsmentioning
confidence: 99%
“…The length and continuity of care through attending the same HIV care center over long periods of time may help a positive trusting relationship to develop, thereby facilitating disclosure. 60 Recommendation #3. Any healthcare provider with an established trust relationship can inquire about IPV Henderson and colleague suggest that a healthcare worker of the same sex is preferable when asking about IPV, 61 while research on IPV screening protocols in reproductive health clinics found that a male inquiring about IPV and a health care provider other than an obstetrician/gynecologist were noted as barriers to disclosure.…”
Section: Recommendation #2 a ''Trust Relationship With The Patient''mentioning
confidence: 99%